Dynamics and Control of Advanced Structures and Machines - Irschik, Hans.; Belyaev, Alexander; Krommer, Michael; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The papers in this volume present and discuss the frontiers in the mechanics of controlled machines and structures. They are based on papers presented at the International Workshop on Advanced Dynamics and Model Based Control of Structures and Machines held in Vienna in September 2015. The workshop continues a series of international workshops held in Linz (2008) and St. Petersburg (2010).
Free and forced vibrations of fuzzy structures -- Resonance of a series of train cars traveling over multi-span continuous -- Stability and supercritical deformation of a circular ring with intrinsic curvature -- Estimation of mechanical properties of micro-lattice panel with irregular cells -- Overview reading and comparing the seismic proof capability of displacement dependent semi-active hydraulic damper and accumulated semi-active hydraulic damper -- On necessary and sufficient conditions for eigenstrain-type control of stresses in the dynamics of force-loaded elastic bodies -- Variational principles for different representations of Lagrangian and Hamiltonian systems -- Hardware-in-the-loop testing of high-speed pantographs using real-time catenary emulation -- Swelling-induced bending of hydrogel bistrips -- Determination of parameters of the external electric circuits providing maximum damping of vibrations of electroelastic bodies -- Forming of woven-reinforced thermoplastic-matrix composites: characterization, modeling, and validation -- Model predictive temperature control of a distribution system for chemicals -- Hidden oscillations in electromechanical systems -- Effect of material layers in a compound circular receiver model design for concentrating solar power -- On multiple support excitation analysis of bridges -- Control of friction by surface microgeometry variation -- Peculiarities of the magnetic behavior of pipe steels with different initial stress-strain states under elastic deformation -- Cable-stayed bridges: a monitoring challenge -- Dynamics and control of motion for systems containing internal moving masses -- Elaborations from the TKB monitoring database -- Reduced order models and localized non-linearity: an approach to the design of meta-structures -- Contact of flexible elastic belt with two pulleys -- Control over internet of oscillations for group of pendulums -- Effect of the load modelling strategy on the dynamic response prediction of bridges subjected to high-speed trains -- Mechanical properties of epoxy resins filled with nano-silica particles.
Keywords: Multibody systems; Vibration; Mechanics, Applied; Mechatronics; Solids; Machinery; Multibody Systems and Mechanical Vibrations; Mechatronics; Solid Mechanics; Machinery and Machine Elements